Clozapine‐induced gastroesophageal rumination in 22q11.2 Deletion Syndrome. A case report on gastroesophageal side effects management without renouncing clozapine's effectiveness - Tommaso Accinni; Marianna Frascarelli; Francesco Ghezzi; Alessia Panzera; Antonino Buzzanca; Martina Fanella; Carlo Di Bonaventura; Luca Carlone; Nicoletta Girardi; Massimo Pasquini; Fabio Di Fabio (Clinical Case Reports, 2021)
Abstract Despite entailing more severe and uncommon side effects in 22q11.2DS compared to idiopathic schizophrenia, we strongly believe that clozapine should continue to be considered the gold standard for all treatment‐resistant schizophrenia, even in 22qDS.